Linear measurement of condyles in edentulous patients with Kennedy classification based on panoramic radiographs - Imanuella, Diandra; Sarifah, Norlaila; Nahzi, Muhammad Yanuar Ichrom; Setyawardhana, Raden Harry Dharmawan; Hasbullah, Irnamanda Dwipura Yakin (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This research is aimed to determine the value of linear measurement of the condyle position in partial edentulous patients of Kennedy classification based on panoramic radiographs at Ulin General Hospital and Gusti Hasan Aman Oral and Dental Hospital. Materials and Methods: This research is a descriptive-analytic study with a cross-sectional study design. The population used in the study is a digital panoramic radiograph from the Radiology Installation of Ulin General Hospital and Gusti Hasan Aman Oral and Dental Hospital from January 2018 - January 2024 database. Condyle linear measurement landmarks used are anterior joint space, superior joint space, and posterior joint space, according to the research of Ikeda and Kawamura (2013). Results: The results showed that the largest AJS value is the Kennedy Class I and the smallest is the Kennedy Class IV. The largest SJS value is the Kennedy class III and the smallest is the Kennedy class IV. The largest PJS value is Kennedy class II and the smallest is Kennedy class I. Based on gender, men's joint space value is bigger than women's. However, a significant difference was found in the PJS value of Kennedy class I patients, whose value for men is smaller than that of women. Conclusion: The condyle linear measurement of partially edentulous patients based on Kennedy classification Class I, II, III, IV has an abnormal condyle position and has experienced disc displacement with reduction.